Polymer nanomedicines with enzymatically triggered activation: A comparative study of in vitro and in vivo anti-cancer efficacy related to the spacer structure - Pechar, Michal; Pola, Robert; Studenovský, Martin; Bláhová, Markéta; Grosmanová, Eliška; Dydowiczová, Aneta; Filipová, Marcela; Islam, Rayhanul; Gao, Shanghui; Fang, Jun; Etrych, Tomáš (Nanomedicine, 2022)
Polymer nanomedicines with anti-tumor activity should exhibit sufficient stability during systemic circulation to the target tissue; however, they should release the active drug selectively in the tumor. Thus, choice of a tumor-specific stimuli-sensitive spacer between the drug and the carrier is critical. Here, a series of polymer conjugates of anti-cancer drugs doxorubicin and pirarubicin covalently bound to copolymers based on N-(2-hydroxypropyl)methacrylamide via various enzymatically cleavable oligopeptide spacers were prepared and characterized. The highest rate of the drug release from the polymer carriers in presence of the lysosomal protease cathepsin B was determined for the copolymers with Val-Cit-Aba spacer. Copolymers containing pirarubicin were more cytotoxic and showed higher internalization rate than the corresponding doxorubicin counterparts. The conjugates containing GFLG and Val-Cit-Aba spacers exhibited the highest anti-tumor efficacy in vivo against murine sarcoma S-180, the highest rate of the enzymatically catalyzed drug release, and the highest cytotoxicity in vitro.
Keywords: nosiče léků; Drug Carriers; nádorové buněčné linie; Doxorubicin; Enzymatic release; Nanomedicine; Mice; Cell Line, Tumor; Antineoplastic Agents; Neoplasms; Polymers; Drug delivery; doxorubicin; protinádorové látky; zvířata; Humans; nádory; nanomedicína; myši; Polymer cancerostatics; polymery; lidé; Animals